Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch : Stellenbosch University, 2019)
Thesis (LLD)--Stellenbosch University, 2019.